Prolonged impacts of sodium glucose cotransporter-2 inhibitors on metabolic dysfunction-associated steatotic liver disease in type 2 diabetes: a retrospective analysis through magnetic resonance imaging - Agena Suzuki; Akinori Hayashi; Satoshi Oda; Rei Fujishima; Naoya Shimizu; Kenta Matoba; Tomomi Taguchi; Takuya Toki; Takeshi Miyatsuka (Endocrine Journal)
The beneficial effects of sodium-glucose cotransporter 2 (SGLT2) inhibitors in people with type 2 diabetes (T2D) and metabolic dysfunction-associated steatotic liver disease (MASLD) have been suggested in several reports based on serological markers, imaging data, and histopathology associated with steatotic liver disease. However, evidence regarding their long-term effects is currently insufficient. In this retrospective observational study, 34 people with T2D and MASLD, treated with SGLT2 inhibitors, were examined by proton density fat fraction derived by magnetic resonance imaging (MRI-PDFF) and other clinical data before, one year after the treatment. Furthermore, 22 of 34 participants underwent MRI-PDFF five years after SGLT2 inhibitors were initiated. HbA1c decreased from 8.9 ± 1.8% to 7.8 ± 1.0% at 1 year (p = 0.006) and 8.0 ± 1.1% at 5 years (p = 0.122). Body weight and fat mass significantly reduced from baseline to 1 and 5 year(s), respectively. MRI-PDFF significantly decreased from 15.3 ± 7.8% at baseline to 11.9 ± 7.6% (p = 0.001) at 1 year and further decreased to 11.3 ± 5.7% (p = 0.013) at 5 years. Thus, a 5-year observation demonstrated that SGLT2 inhibitors have beneficial effects on liver steatosis in people with T2D and MASLD.